PENERAPAN STRATEGI HEMBUSAN ANGIN KENCANG UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS V SEKOLAH DASAR NEGERI 20 PEKANBARU - Windy Anggraini (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract: This research aimed at knowing the enhancement of student learning motivation on Indonesian subject at the fifth grade of State Elementary School 20 Pekanbaru. This research was instigated by the low of student learning motivation seen on the ongoing learning process that students did not pay attention to the teacher explanation and not want to question. This research was a Classroom Action Research. The subjects of this research were teachers and the fifth grade students, and the object was Hembusan Angin Kencang strategy in increasing student learning motivation on Indonesian subject. This research was conducted for two circles, every circle comprised two meetings. Observation, and documentation were the techniques of collecting the data. Keywords : Strategy, Hembusan Angin Kencang, Student Learning Motivation